Effect of vibration frequency on frictional resistance of brain tissue during vibration-assisted needle insertion. (December 2020) - Wu, Wenhao; Xu, Changfeng; Pan, Chunyang; Huang, Zhixiang; Zhou, Jun; Huang, Panling
Highlights: Vibration-assisted insertion can be used in deep brain stimulation surgery. The trend of friction force during vibration-assisted insertion is described. Vibration assisted insertion can effectively reduce the friction during insertion. There is an optimal frequency that minimizes the friction in vibration-assisted insertion. Abstract: Deep brain stimulation (DBS) is an effective treatment for Parkinson's disease. The cannula insertion process plays an important role in DBS. The friction force during needle insertion influences the precision of the insertion and the degree of damage to the brain tissue. This paper proposes a method of longitudinal vibration assisted insertion to reduce the friction during insertion and improve the effects of the insertion. Cannulas were inserted into twenty eight pig brains at multiple frequencies and fixed amplitudes, and the resulting friction force was measured. On this basis, the LuGre model was used to analyze the friction force trend under vibration-assisted conditions. The frictional forces of vibration-assisted insertion with frequencies ranging from 200–1200 Hz and an amplitude of 1 μm were measured. The results show that the friction between the needle shaft and the tissue is smaller with vibration than without vibration. In this experiment, the friction is reduced by up to 24.43%. The friction force trend of vibration-assisted insertion conforms to the simulation results of the LuGre model.